2018
DOI: 10.1111/apps.12145
|View full text |Cite
|
Sign up to set email alerts
|

Tell Me What I Wanted to Hear: Confirmation Effect in Lay Evaluations of Financial Expert Authority

Abstract: In real life, people engage in interactive decision processes by consulting with experts. However, before taking advice, they must recognise the authority of an expert to assess the quality of the advice. The main goal of this research was to investigate how the confirmation effect affects lay evaluations of the epistemic authority of financial experts. Experiment 1 showed that lay people tend to ascribe greater epistemic authority to those experts whose advice confirms peoples opinions, both measured and mani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
15
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(25 citation statements)
references
References 70 publications
3
15
0
1
Order By: Relevance
“…Biased evaluation of experts was shown in empirical work reported in Zaleskiewicz and Gasiorowska (2018;cf. Zaleskiewicz et al, 2016, Study 3).…”
Section: Evaluation Of Expert Opinionsmentioning
confidence: 97%
“…Biased evaluation of experts was shown in empirical work reported in Zaleskiewicz and Gasiorowska (2018;cf. Zaleskiewicz et al, 2016, Study 3).…”
Section: Evaluation Of Expert Opinionsmentioning
confidence: 97%
“…Our recent research (Zaleskiewicz & Gasiorowska, 2018; Zaleskiewicz, Gasiorowska, Stasiuk, Maksymiuk, & Bar-Tal, 2016) has shown that decision-makers, when evaluating the financial expertise of prospective advisors, are vulnerable to preferring advice that is consistent, as opposed to inconsistent, with their own beliefs. In brief, we investigated how financial recommendations concerning individual investing on the stock market were perceived depending on whether they were, or were not, consistent with laypeople’s own opinions of this financial activity (Zaleskiewicz & Gasiorowska, 2018).…”
Section: Confirmation Effect In Evaluating Financial Experts’ Authoritymentioning
confidence: 99%
“…Our recent research (Zaleskiewicz & Gasiorowska, 2018; Zaleskiewicz, Gasiorowska, Stasiuk, Maksymiuk, & Bar-Tal, 2016) has shown that decision-makers, when evaluating the financial expertise of prospective advisors, are vulnerable to preferring advice that is consistent, as opposed to inconsistent, with their own beliefs. In brief, we investigated how financial recommendations concerning individual investing on the stock market were perceived depending on whether they were, or were not, consistent with laypeople’s own opinions of this financial activity (Zaleskiewicz & Gasiorowska, 2018). In other words, we examined the degree to which lay evaluations of financial experts’ epistemic authority—defined in terms of “the extent to which an individual is inclined to treat a source’s information as incontrovertible evidence for her or his judgment” (Kruglanski, 2012, p. 212)—expressed “my side” thinking.…”
Section: Confirmation Effect In Evaluating Financial Experts’ Authoritymentioning
confidence: 99%
See 1 more Smart Citation
“…Los individuos que atribuyen el consenso reducen la carga cognitiva y confían en la deducción del grupo. Es decir, la representación compartida influye en la atribución de los sujetos a los comportamientos (Kelley, 1967;Zaleskiewicz & Gasiorowska, 2018).…”
Section: La Cognición Social Y La Construcción Del Conocimientounclassified